Is Ethicality Itself a Boundary Condition for Ethicality: The Complementary Role of Employees’ Exchange Ideology and Moral Awareness in Restricting the Effect of Ethical Leadership in Reducing Workplace Deviance - Nasim, Aisha; Siddiqui, Danish Ahmed (Global Journal of Educational Studies, 2024)
Ethical leadership (EL) seems to be effective in reducing workplace deviance, questions remain as to whether its benefits are consistent across all situations. Specifically, whether its effectiveness remained in an already ethical environment. In this investigation, we explore two important boundary conditions of ethical leadership that are themselves related to ethicality. We first explore how employees’ moral awareness (MA) may lessen the need for ethical leadership. Drawing on substitutes for leadership theory, we suggest that when individuals already possess a heightened level of moral awareness, ethical leadership’s role in reducing deviant actions may be reduced. We also contended that Employees’ Exchange Ideology - the strength of an employee’s belief that the work effort should depend on treatment by the organization- also reduces EL effectiveness. This norm of reciprocity may not be ethical, as the leader’s positive or negative efforts towards employees may divert them from doing what is morally right to reciprocate. However, not all individuals value reciprocity to the same degree, hence higher Employees’ Exchange Ideology (EEI) may be another boundary condition of EL effectiveness. We conceptualize this framework by modifying Gok et. al. (2017) model to add Employees’ Exchange Ideology as a moderating factor along with Moral Awareness. Workplace Deviance was measured by organizational directed deviance (OD) and supervisor directed deviance (SD). Empirical validity was established by conducting a survey using a close-ended questionnaire. Data was collected from 310 employees working in different organizations in Pakistan and was analyzed using confirmatory factor analysis and structured equation modeling. Results indicated a significant negative complementarity of EEI, in the effect of EL on both dimensions of workplace deviance. This suggested, higher EEI seems to limit the effect of EL on organizational and supervisor-directed deviance. However, the moderating effect of MA was not substantiated for Pakistan. EEI also seems to have a positive effect on both OD and SD, while, SD seems to have a positive effect on OD. Interestingly, EL seems to be causing rather than reducing both OD and SD in the Pakistani environment.